1997
DOI: 10.1111/j.1553-2712.1997.tb03659.x
|View full text |Cite
|
Sign up to set email alerts
|

Underrecognition of Cervical Neisseria gonorrhoeae and Chlamydia trachomatis Infections in the Emergency Department

Abstract: Objectives: 1 ) To quantify the frequency of underrecognized Neisseria gonorrhoeae and Chlamydia trachomatis cervical infections in women tested in the ED, 2) to describe and compare the characteristics of those treated and not treated during the initial visit, and 3) to quantify the delay interval until treatment was provided. Methods: A 2-year, retrospective consecutive case series was performed from June 1, 1992, to May 31, 1994. There were 148 women with 2 1 discrete occurrence of culture-proven cervical N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 4 publications
2
26
2
Order By: Relevance
“…8,13 Emergency physicians practicing in GC/CT-prevalent endemic areas who see patients with these diagnoses should have a higher index of suspicion and consider empiric treatment. This study confirms the magnitude of underrecognized STDs in the ED as shown by Yealy et al 7 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…8,13 Emergency physicians practicing in GC/CT-prevalent endemic areas who see patients with these diagnoses should have a higher index of suspicion and consider empiric treatment. This study confirms the magnitude of underrecognized STDs in the ED as shown by Yealy et al 7 …”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon was also experienced in Yealy et al's study, where treatment for 25% of their positive female patients could not be documented due to an inability to locate the patients. 7 Some of the patients in our study refused treatment; it is unknown whether they received treatment elsewhere. These shortcomings confirm the missed opportunities to treat patients at their initial presentations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, clinical practice in our ED was similar to that of others: notify patients with an STI only if they were not treated at their visit. 5 We found that adolescent women who believed they had an STI were more likely to abstain from sexual activity and to notify their partners than those who were unaware of their STI. However, women who were treated with antibiotics but did not believe they tested positive for STIs did not change their behavior.…”
mentioning
confidence: 69%
“…After an ED visit, some estimate that only 29% of untreated women are treated within 14 days, and 60% are lost to follow-up. 5,7,[8][9][10] Sexually transmitted disease clinics report that ∼50% are treated within 14 days, and 20% to 30% are lost to follow-up. [8][9][10] In our adolescent clinic, we contacted 69% of untreated women within 7 days, and ,10% were lost to follow-up.…”
mentioning
confidence: 99%